2018
DOI: 10.1002/cncr.31746
|View full text |Cite
|
Sign up to set email alerts
|

Response to therapeutic monoclonal antibodies for multiple myeloma in African Americans versus whites

Abstract: BACKGROUND: Myeloma occurs disproportionately in African Americans, with disparities in outcomes potentially caused by access to care, cytogenetics, and immunity. A gap in knowledge of immune function dissimilarities between African Americans and whites exists. Data for other diseases suggest innate differences in immunity and inflammatory markers, with potential implications for therapeutic monoclonal antibodies reliant on secondary immune activation for activity. METHODS: Patients receiving daratumumab or el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We appreciate the praise and thoughtful commentary from Mr. Fiala regarding our report on our experience with the therapeutic monoclonal antibodies daratumumab and elotuzumab in African American patients compared with white patients treated at the Winship Cancer Institute of Emory University . He expressed concern with our statistics and the conclusions we drew, specifically that a lack of statistical significance in our analyses does not necessarily mean no difference exists, or, stated another way, that the numeric differences we observed in the retrospective analysis may be real, and therefore clinically significant.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…We appreciate the praise and thoughtful commentary from Mr. Fiala regarding our report on our experience with the therapeutic monoclonal antibodies daratumumab and elotuzumab in African American patients compared with white patients treated at the Winship Cancer Institute of Emory University . He expressed concern with our statistics and the conclusions we drew, specifically that a lack of statistical significance in our analyses does not necessarily mean no difference exists, or, stated another way, that the numeric differences we observed in the retrospective analysis may be real, and therefore clinically significant.…”
mentioning
confidence: 91%
“…We considered this as well in our conclusion. Because our study was a retrospective analysis of a fixed cohort, we unfortunately did not have the ability to prospectively determine power calculations. We appreciate the power concerns noted by Mr. Fiala, and agree that additional studies are needed to assert definitive conclusions, as we stated.…”
mentioning
confidence: 99%
“…The authors found that the respective overall response rates (ORRs), defined as a partial response or better, to single‐agent daratumumab was only 11.8% (2 of 17 patients) for African Americans compared with 37.9% (11 of 29 patients) for whites. Similarly, the ORR for African American patients receiving the combination of elotuzumab, lenalidomide, and dexamethasone was only 44.4% (4 of 9 patients) compared with 60% (15 of 25 patients) for whites . However, neither of these differences was statistically significant, leading the authors to conclude that both races have similar responses to treatment with MoAbs.…”
mentioning
confidence: 96%
“…In the current study, it is possible that the findings are purely spurious. They also could be due to imbalances in patient demographics: African American patients were >3 times more likely to have International Staging System stage III disease compared with white patients . Additional studies are needed to adjudicate this.…”
mentioning
confidence: 99%
See 1 more Smart Citation